Genome-Wide DNA Methylation in Policemen Working in Cities Differing by Major Sources of Air Pollution - Honkova, Katerina; Rossnerova, Andrea; Chvojkova, Irena; Milcova, Alena; Margaryan, Hasmik; Pastorkova, Anna; Ambroz, Antonin; Rossner, Pavel; Jirik, Vitezslav; Rubes, Jiri; Sram, Radim J; Topinka, Jan (International journal of molecular sciences, 2022)
DNA methylation is the most studied epigenetic mechanism that regulates gene expression, and it can serve as a useful biomarker of prior environmental exposure and future health outcomes. This study focused on DNA methylation profiles in a human cohort, comprising 125 nonsmoking city policemen (sampled twice), living and working in three localities (Prague, Ostrava and Ceske Budejovice) of the Czech Republic, who spent the majority of their working time outdoors. The main characterization of the localities, differing by major sources of air pollution, was defined by the stationary air pollution monitoring of PM2.5, B[a]P and NO2. DNA methylation was analyzed by a genome-wide microarray method. No season-specific DNA methylation pattern was discovered; however, we identified 13,643 differentially methylated CpG loci (DML) for a comparison between the Prague and Ostrava groups. The most significant DML was cg10123377 (log2FC = -1.92, p = 8.30 × 10-4) and loci annotated to RPTOR (total 20 CpG loci). We also found two hypomethylated loci annotated to the DNA repair gene XRCC5. Groups of DML annotated to the same gene were linked to diabetes mellitus (KCNQ1), respiratory diseases (PTPRN2), the dopaminergic system of the brain and neurodegenerative diseases (NR4A2). The most significant possibly affected pathway was Axon guidance, with 86 potentially deregulated genes near DML. The cluster of gene sets that could be affected by DNA methylation in the Ostrava groups mainly includes the neuronal functions and biological processes of cell junctions and adhesion assembly. The study demonstrates that the differences in the type of air pollution between localities can affect a unique change in DNA methylation profiles across the human genome.
Keywords: látky znečišťující vzduch; Police; celogenomová asociační studie; Air Pollution; vystavení vlivu životního prostředí; Air Pollutants; Česká republika; Middle Aged; mužské pohlaví; air pollution; znečištění ovzduší; Environmental Exposure; Adult; Czech Republic; epigenetics; environment; molecular epidemiology; DNA methylation; ženské pohlaví; Humans; metylace DNA; lidé středního věku; DNA Methylation; dospělí; policie; Female; Genome-Wide Association Study; lidé; Male